Incontinentia pigmenti with neurologic and oculodental disorders - Jorge Arturo Avina Fierro; Daniel A Hernandez Avina (Wolters Kluwer Medknow Publications, 2016)
Incontinentia pigmenti is a genodermatosis with X-linked dominant inheritance, characterized by cutaneous, neurologic, ophthalmologic, and dental abnormalities with a pattern suggestive of somatic mosaicism. We describe a 21-month-old girl showing characteristic cutaneous findings of incontinentia pigmenti in chronic evolution of hyperpigmented, hypopigmented, and atrophic stages, linear and whorled pattern involving the Blaschko's lines. The patient has history of seizures, and electroencephalography showed epileptiform discharges at temporal lobule, cranial magnetic resonance imaging revealed cerebral dysgenesis, neuronal migration disorder, and hypoplasia of the corpus callosum. She has motor and mental delay with spastic quadriplegia, and ophthalmologic loss of central vision by ischemic optic neuropathy with decreased blood flow to eye's optic nerve. The dermatologic features were confirmed by skin biopsy that showed slight atrophy and some scattered apoptotic cells in the epidermis, epidermal hypopigmentation, and reduced melanocyte number, these histological features confirmed the genodermatosis diagnosis: Bloch-Sulzberger syndrome.